Comparative study of oral methotrexate and acitretin in the treatment of palmoplantar psoriasis - Parsam, Suman Babu; Ireddy, Shankargowda (International Journal of Research in Medical Sciences, 2017)
Background:Psoriasis is chronic inflammatory skin condition. Palmoplantar psoriasis is a type where lesions are present on the palms and soles. This type affects patient’s quality of life and is difficult to treat. Topical modes of treatment are not so effective and produce inadequate response. Systemic drugs are necessary in the treatment of moderate to severe disease. The objective was to compare the efficacy of oral methotrexate and acitretin in treatment of moderate to severe palmoplantar psoriasis and there side effects. Methods:50 patients with palmoplantar psoriasis were randomized into 2 groups. Patients in group I received oral methotrexate and patients in group II received acitretin for 3 months. Baseline grading was done with Modified Psoriasis Area Severity Index (MPASI) score. MPASI score was assessed monthly. Scores at the beginning and at the end of 3 months of treatment were compared. Quality of life was assessed using a questionnaire. Results:MPASI score in group I was 57.15 ± 17.17 at baseline and 14.50 ± 13.55 at the end of 3rd month. The difference in scores before and after treatment was statistically significant. MPASI score in group II was 57.76 ± 18.60 at baseline and 21.30 ± 8.168 at the end of 3rd month. Intragroup analysis showed statistically significant difference before and after treatment. There was significant improvement in the quality of life after treatment. Conclusion:Oral methotrexate reduces the lesions faster than acitretin. Both oral methotrexate and acitretin are highly effective in treating palmoplantar psoriasis and in improving patient’s quality of life.